Dentoalveolar Fractures: New Orthodontic Protocol Proposal and Pilot Study. Issue 8 (November 2020) - Dell'Aversana Orabona, Giovanni; Perrotta, Stefania; Lo Giudice, Giorgio; Bocchino, Tecla; Valletta, Rosa; Abbate, Vincenzo; Califano, Luigi
Abstract : Abstract: The goal of fracture treatment that includes the dentoalveolar process is to obtain the anatomic bone healing and the pre-injury occlusion restoration with functional and aesthetic recovery, avoiding dental or periodontal lesions. Fractures activates, in the damaged tissue, the Regional Acceleratory Phenomenon, a physiological healing process that can also be activated during orthodontic overloads. Orthodontic treatment in the traumatized area could exploit this phenomenon in order to sustain the cellular activity. The aim of this study is to propose a treatment protocol for dentoalveolar fractures based on the use of orthodontics in order to sustain the physiological healing process known as Regional Acceleratory Phenomenon. The authors present 2 cases of an 18 year old woman and 23 year old man affected by dentoalveolar fracture. The operative protocol the authors applied foresaw three steps of treatment: orthodontic brackets application, surgery, orthodontic treatment. The patients showed complete healing at the 3 months follow-up and were treated up to 18 months for further orthodontic treatment. The operative protocol proposed by the Authors appears to be a rational choice since it allows a single orthodontic device to be an "active splinting system", with fast application time, good acceptance by the patient, low complications rate; moreover, it produces any planned dental movements for further orthodontic treatments. Abstract : Supplemental Digital Content is available in the text